Optical coherence tomography imaging of the patent ductus arteriosus: First known uses in congenital heart disease. Issue 2 (28th October 2014) - Hill, James A.; Mahadevaiah, Guruprasad; Jenkins, Michael W.
<x xml:space="preserve">Abstract</x> Background Angiography is used to assess ductal morphology and caliber during interventional closure of the ductus arteriosus. We are evaluating the use of optical coherence tomography (OCT) to evaluate ductal anatomy given the potential benefit of superior resolution and lower radiation. Methods Standard angiograms were performed on two patients with patent ductus arteriosus prior to device occlusion. OCT was then used to obtain high‐resolution three‐dimensional vessel reconstructions. Devices were chosen based on angiographic measurements. Results OCT resulted in excellent three‐dimensional anatomic definition, with elliptical narrowest lumenal measurements of 2.2 × 3.1 mm and 1.6 × 2.3 mm, respectively, compared with angiographic measurements of 2.6 and 1.4 mm. Conclusions To our knowledge, this is the first reported use of OCT use in pediatric patients outside the coronaries, and in patients with congenital heart disease. We found OCT imaging of the PDA to be feasible, and only used a small amount of additional radiation and contrast. The three‐dimensional OCT reconstructions provided additional anatomic information that could potentially improve device selection, and in both cases may have led to choosing larger devices than what was chosen based on angiography. In addition, once the technique is perfected, little or no angiography or fluoroscopy will be required to perform imaging runs, and only a small injection of contrast appears to be sufficient for vessel imaging. However, there are certain limitations to OCT imaging that are unlikely to make it the method of choice specifically for imaging the patent ductus arteriosus, but we have shown its ability to provide high resolution imaging in a relatively simple fashion which may prove useful for other purposes. © 2014 Wiley Periodicals, Inc.